2016
DOI: 10.4172/2314-7326.1000218
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Neuro-Chikungunya in Northeastern Brazil

Abstract: Chikungunya virus, an alphavirus often associated with large epidemic outbreaks, has a serious social impact. The main symptoms are fever, rash and arthralgia, but recently neurologic complications have been described as an important cause of morbidity. During a large outbreak in at least five towns in poor states of the Brazilian northeast over recent months, 22 patients with chikungunya confirmed by serologic tests who presented some degree of neurologic involvement were assessed in our department. Changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…However, it has not been confirmed until now that CHIKV is neurotropic, with several studies showing that often patients have neurological and psychiatric symptoms in the acute and sometimes in the chronic phase of the disease, such as daily chronic headache and depressive and anxiety disorder, thereby substantially reducing their quality of life [1,5].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it has not been confirmed until now that CHIKV is neurotropic, with several studies showing that often patients have neurological and psychiatric symptoms in the acute and sometimes in the chronic phase of the disease, such as daily chronic headache and depressive and anxiety disorder, thereby substantially reducing their quality of life [1,5].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that adequate clinical management in the acute phase of the disease can prevent or even avoid more serious complications [1]. Considering all the dysfunction caused by the disease, it would be ideal for all infected patients to have monthly follow-ups with a specialized team composed of a general practitioner, rheumatologist, psychiatrist, psychologist, physiotherapist and occupational therapist to identify and adjust factors related to the impaired quality of life of patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Chikungunya occurred as a Major epidemic form in Bangladesh after a gap of 6 years in 2017. Chikungunya fever is an acute illness, mainly characterized by acute fever and severe joint pain [4] and has various complications like rheumatological, neurological, psychological, and dermatological, and even multi-organ failure.…”
Section: Introductionmentioning
confidence: 99%